Enhanced photocatalytic activity and mechanism of Ti3C2−OH/Bi2WO6:Yb3+, Tm3+ towards degradation of RhB under visible and near infrared light irradiation. (January 2020) - Fang, Hongjun; Pan, Yusong; Yin, Minyuan; Pan, Chengling
Graphical abstract: Highlights: Ti3 C2 -OH/Bi2 WO6 :Yb 3+, Tm 3+ was prepared via a facile hydrothermal method. Ti3 C2 -OH/Bi2 WO6 :Yb 3+, Tm 3+ composites accompanied 2D/2D heterojunction with grid-like porous hierarchical structure. Ti3C2 -OH/Bi2 WO6 :Yb 3+, Tm 3+ composite shows significant enhancement on photocatalytic activity. Abstract: It is an effective method to explore full spectrum responsive photocatalyst for improving their photocatalytic activity. Herein, Ti3 C2 −OH/Bi2 WO6 :Yb 3+, Tm 3+ composites were successfully synthesized via a facile hydrothermal method. The resultant Ti3 C2 −OH/Bi2 WO6 :Yb 3+, Tm 3+ composites accompanied 2D/2D heterojunction with grid-like porous structure present a significant enhancement of photoactivity towards degradation of RhB under visible and NIR light irradiation. Specifically, the 0.2-Y/T-TB2.8 composite exhibits the best photocatalytic activity for RhB removal, in which the RhB degradation efficiency was 99.8% (Vis-NIR, 30 min), 91% (Vis, 30 min), and 48% (NIR, 160 min). The excellent photocatalytic activity of the composite is attributed to the grid-like porous structure endowing it with an enhanced RhB adsorption, favorable charge separation resulting from the outstanding conductivity of the Ti3 C2 −OH, and up-conversion mechanism via energy level transition of Yb 3+ /Tm 3+ . In addition, the radical capture experiments verified that the hole (h + ) plays the important role for degradation of RhB.